English Teachers’ Teaching Strategies to Promote Students’ Writing Skills in Online Learning Circumstances - Giyaning Rahma; Sumardi Sumardi; Endang Setyaningsih (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to look into how EFL teachers use teaching strategies and how they use those strategies to help students improve their writing skills during online learning. A qualitatively guided phenomenological approach is used to study three teachers and students from senior high school. The research includes interviews, questionnaires, and document analysis. The researcher then analyzed the data using techniques such as data condensation, data display, and drawing conclusions or verification. The findings show that teachers used a variety of teaching strategies in teaching writing, such as demonstrating, motivating, providing feedback, and evaluating students' tasks. Moreover, the teachers used Google Meet to give students direct instruction about teaching materials, and they used collaborative teaching by assigning students tasks to complete individually or in groups or discussions. The final strategy that teachers employ is self-directed teaching, in which teachers assign students one specific material to study independently using an online source. Using those strategies, students were helped to improve their writing skills.